2012
DOI: 10.2298/jmmb111219031m
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermic reduction of electric arc furnace dust and calcination of waelz oxide by semi-pilot scale rotary furnace

Abstract: The paper gives a common outline about the known recycling techniques from electric arc furnace dusts and describes an investigation of a pyrometallurgical process for the recovery of zinc and iron from electric arc furnace dusts (EAFD). In the waelz process, the reduction of zinc and iron from the waste oxides using solid carbon (lignite coal) was studied. In the reduction experiments; temperature, time and charge type (powder and pellet) were investigated in detail. It was demonstrated that zinc and ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Several routes were used to extract metal from some metallic oxide such as carbo-thermic reduction 26 , electrolysis from molten salt for some active metals 27 and carbo-chlorination. As it was thermodynamically favorable for the formation of chlorides, Ilic et al 28 discussed the chlorination of nickel oxides and nickel ferrites with or without additives and found that the chlorination degree of Ni, Fe, Cr increased with the increase in the quantity of coal.…”
Section: Procedures Of the Carbo-chlorination Of Sio2mentioning
confidence: 99%
“…Several routes were used to extract metal from some metallic oxide such as carbo-thermic reduction 26 , electrolysis from molten salt for some active metals 27 and carbo-chlorination. As it was thermodynamically favorable for the formation of chlorides, Ilic et al 28 discussed the chlorination of nickel oxides and nickel ferrites with or without additives and found that the chlorination degree of Ni, Fe, Cr increased with the increase in the quantity of coal.…”
Section: Procedures Of the Carbo-chlorination Of Sio2mentioning
confidence: 99%
“…Several pyrometallurgical and hydrometallurgical processes (Jankovi et al, 2014;Langová and Matýsek, 2010;Morcali et al, 2012;Shawabkeh, 2010) have been proposed for the treatment of zinc ferrites. Pyrometallurgical methods are costly owing to high energy consumption and their emissions of toxic gases are considered an environmental problem; hydrometallurgical methods are preferred for process economy and environmental reasons (Copur et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The pyrometallurgical methods for treatment of the EAF dust are preferred, because of the difficulty in leaching of the Franklinite (ZnFe 2 O 4 ) [3][4][5]. Carbon reduces the leaching residue into iron and zinc at high temperatures, so the combination of these two methods can be applied [6]. Mill scale is generated in steelmaking industry; it mainly consists of iron oxides and relatively small amounts of the sulfur, phosphorus, and alkalis [7].…”
Section: Introductionmentioning
confidence: 99%